Durable purchases over the later life cycle - Martin Browning; Thomas F. Crossley; Melanie Lührmann (Institute for Fiscal Studies (IFS), 2012)
We investigate life cycle patterns of demand for services from household durables using UK panel data. We take careful account of prices, demographics, labour supply and health. Demand for consumer electronics rises with age, while the demand for household appliances is flat. These findings contrast with the well documented decline in nondurable consumption at older ages, and suggest that studies that estimate the overall discount rate from nondurable consumption may underestimate consumer patience and the savings required to fund retirement. We also find important nonseparabilities between the demand for durables, labour supply and health status.
Keywords: E21; D12; 330; life cycle model; consumer behaviour; durables